Psychosis: clinical insight and beliefs in immigrants in their first episode. Issue 2 (10th December 2015) - Berg, Akiah Ottesen; Barrett, Elizabeth Ann; Nerhus, Mari; Büchman, Camilla; Simonsen, Carmen; Færden, Ann; Andreassen, Ole A.; Melle, Ingrid
Abstract: Aim: Lack of insight into illness is frequent in psychotic disorders and seen as part of their primary pathology. The recognition of symptoms as psychotic, and beliefs about treatment alternatives, is also influenced by socio‐cultural factors. Here we examined clinical insight into illness and beliefs about psychosis in immigrants in their first episode of psychosis compared with a reference group. Methods: A total of 277 first‐episode psychosis participants were recruited to this cross‐sectional study; 40 first‐ and 40 second‐generation immigrants from Europe, Americas and Oceania ( n  = 37), Asia including Turkey ( n  = 28) or Africa ( n  = 15). The Birchwood Insight Scale was used to measure clinical insight and 'The Attitudes and Beliefs about Mental Health Problems' schizophrenia version to assess socio‐cultural beliefs. Results: Immigrants did not differ from the reference sample in clinical insight. After controlling for education level, first‐generation immigrants were less likely to recognize psychotic symptoms (odds ratio (OR) 2.9; Wald = 8.977, degrees of freedom (d.f.) 1, P  = 0.003) and viewed hospitalization (OR 5.2; Wald = 20.388, d.f. 1, P  = 0.001) and treatment by a psychiatrist (OR 4.9; Wald = 6.609, d.f. 1, P  = 0.01)) as less beneficial than the reference group. Immigrants from Asia held more alternative explanations (OR 0.3; Wald = 6.567, d.f. 1, P  = 0.010). There were significantly stronger associations between clinical insight and socio‐cultural beliefs in the reference group. Conclusions: Socio‐cultural beliefs about psychosis in immigrants in first‐episode psychosis call for more tailored information to this group, and emphasize the importance of treatment interventions involving both a cultural and personal perspective of insight.